Evaluation of a randomized intervention to delay sexual initiation among fifth-graders followed through the sixth grade - Koo, Helen P. (2011)
US adolescents initiate sex at increasingly younger ages, yet few pregnancy prevention interventions for children as young as 10–12 years old have been evaluated. Sixteen Washington, DC schools were randomly assigned to intervention versus control conditions. Beginning in 2001/02 with fifth-grade students and continuing during the sixth grade, students completed pre-intervention and post-intervention surveys each school year. Each year, the intervention included 10–13 classroom sessions related to delaying sexual initiation. Linear hierarchical models compared outcome changes between intervention and control groups by gender over time. Results show the intervention significantly decreased a rise over time in the anticipation of having sex in the next 12 months among intervention boys versus control boys, but it had no other outcome effects. Among girls, the intervention had no significant outcome effects. One exception is that for both genders, compared with control students, intervention students increased their pubertal knowledge. In conclusion, a school-based curriculum to delay sexual involvement among fifth-grade and sixth-grade high-risk youths had limited impact. Additional research is necessary to outline effective interventions, and more intensive, comprehensive interventions may be required to counteract adverse circumstances in students’ lives and pervasive influences toward early sex. ClinicalTrials. gov identifier: NCT00341471